Um estudo das oportunidades e desafios envolvidos na utilização de serviços de Cloud Computing - Madureira Junior, José Roberto (2014)
The following research focuses on the widespread use of Cloud Computing as a result of a major market boost due to the latest trends and needs. It has progressed as a result of advanced technology providing businesses a high standard of service as well as being of great benefit to its users. This final work is aimed at demonstrating users and potencial ones the benefits as well as the possibilities and challenges involved in the use of Cloud Computing and therefore allow them to identify, understand and manage such a service. As a result users shall be able to hire services involving a low risk factor in addition to implementing an appropriate workload. Due to the lack of information regarding Cloud Computing services, we believe that this research can provide users a valuable contribution in clarifying and highlighting both the potentiality and benefits involved as well as analysing the reasons they have not been able to benefit from them so far. We would like to point out that when we searched for literature regarding specifically the service users no significant data was collected. As a result we strongly believe that if such material is published it will represent a significant contribution towards both the users and the academic community. At first we carried out a state of the art study regarding Cloud Computing, identifying the potential benefits involved in providing such a service as well as the impact such a model has had on the information technology scenario. Then we implemented the case study metodology in which three real cases with the model in use were closely followed. Reference is also made to prestigious companies with a solid background within their market segment and the respective services they provide. This will allow the users to obtain the necessary backup in order to be able to previously analyse the ideal sevice which will suit their needs. We concluded that companies seem to be cautious about implementing such a structure due to their concern about mainly operational and safety measures. Cloud Computing´s progress depends on such an acceptance. Therefore this text focuses on identifying and analysing the challenges and benefits involved in implementing such a model. Research has been done with the specific aim of offering a wide range of businesses an overview of Cloud Computing as well as enabling users to overcome any difficulties